Using Governance to Elevate Voluntary and Community Sector Representation - Andrea Bentz; Elizabeth Tanguay; Dania Versailles; Sylvie Lefebvre (International Journal of Integrated Care)
Archipel Ontario Health Team (OHT) developed as part of the provincial call to organize health and social service providers into integrated care delivery systems. With nearly 70 multi-disciplinary and multi-sectoral partners, unequal power dynamics must be considered when creating governance structures. With the aim of collaboratively elevating the voice of voluntary and community sector partners, Archipel OHT deliberately implemented a sustainable integrated governance strategy that encourages community and voluntary sector leadership and equitable shared decision-making. This perspective paper describes applied strategies, lessons learned, and efforts to maintain an environment that prioritizes their representation.